2022
DOI: 10.12669/pjms.38.3.4823
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Neural Therapy on shoulder dysfunction and pain in supraspinatus tendinopathy

Abstract: Objectives: To investigate the effect of 1% procaine injection, which is used in neural therapy, on shoulder pain and dysfunction in patients diagnosed with supraspinatus tendinopathy. Methods: The Range of Motion values, Visual Analog Scale and the QuickDASH Scale scores of 70 patients, who were diagnosed with musculus supraspinatus tendinitis based on magnetic resonance imaging findings, were analyzed. The data of the scales obtained before neural therapy and at the follow-up visit at four weeks after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Ayrıca kronik KBAS ile karşılaştırıldığında erken KBAS tedaviye daha az dirençlidir ve bu nedenle prognozu daha iyidir. Tedavinin amacı sadece ağrı ve rahatsızlığın iyileştirilmesi değil, aynı zamanda fonksiyonel restorasyon ve sakatlığın önlenmesidir (9,10) Nöral terapi uygulamasının amacı lokal anesteziklerin anti-inflamatuar, analjezik, sempatolitik etkilerinden faydalanarak hücre zarı aktivasyon potansiyeli üzerine etki ederek dokuların düzensiz perfüzyonunu arttırmak, organ veya sistemlerin yıkım ürünlerini ortadan kaldırmaktır (5). Egli ve arkadaşlarının çalışmasında kronik sırt ağrısı olan 280 hasta değerlendirilmiş ve nöral terapinin kronik ağrı tedavisinde etkili bir yöntem olduğu bildirilmiştir (11).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Ayrıca kronik KBAS ile karşılaştırıldığında erken KBAS tedaviye daha az dirençlidir ve bu nedenle prognozu daha iyidir. Tedavinin amacı sadece ağrı ve rahatsızlığın iyileştirilmesi değil, aynı zamanda fonksiyonel restorasyon ve sakatlığın önlenmesidir (9,10) Nöral terapi uygulamasının amacı lokal anesteziklerin anti-inflamatuar, analjezik, sempatolitik etkilerinden faydalanarak hücre zarı aktivasyon potansiyeli üzerine etki ederek dokuların düzensiz perfüzyonunu arttırmak, organ veya sistemlerin yıkım ürünlerini ortadan kaldırmaktır (5). Egli ve arkadaşlarının çalışmasında kronik sırt ağrısı olan 280 hasta değerlendirilmiş ve nöral terapinin kronik ağrı tedavisinde etkili bir yöntem olduğu bildirilmiştir (11).…”
Section: Discussionunclassified
“…Lokal , segmental, derin enjeksiyonlar şeklinde tedavide prokain ya da lidokain kullanılır. Kas iskelet sistemi hastalıklarında sıklıkla tercih edilen bir tedavi yöntemidir (4,5).…”
Section: Introductionunclassified
“…Most studies, including RCTs and reviews, were related to acupuncture treatment for shoulder pain. Some of these included studies reported that acupuncture is effective in relieving shoulder pain, 43,44 whereas others did not mention whether it is effective or ineffective in treating shoulder pain 26 or whether it is ineffective in treating shoulder pain; 45 Different acupuncture methods or tools have been used in studies on acupuncture to treat shoulder pain, such as bee venom acupuncture, 46 auricular acupuncture, 47 fire needles, 48,49 small needle-knife, 41 thread-embedding acupuncture, 50 warm-needle moxibustion and heat-sensitive moxibustion, 6 electroacupuncture, 51 and sharp-hook acupuncture. 52 Some studies are related to summarizing the common acupoints rules of acupuncture treating and moxibustion in shoulder pain, such as Tiaokou; 53 Chengshan acupoint; 54 Baihui acupoint; 55 Ashi points stimulation; 56 Zhongfu, Tianfu, Xiabai, Binao, Naohui, Jianliao, and Xiaoluo points; 57 distal-needling acupuncture; 58 and acupuncture on the opposite side of the pain to treat long-term shoulder pain.…”
Section: Current Research Hotspots and Frontiersmentioning
confidence: 99%
“…In the last session, the second session protocol was repeated. 20 All treatment sessions were performed by a physical therapy specialist with a certificate of neural therapy application. The range of motion (ROM) was measured based on the guidelines of Kendall et al; cervical flexion, extension, rotation and lateral flexion ROM measurements were made actively, each measurement was repeated three times and average values were calculated.…”
Section: Treatment Protocolmentioning
confidence: 99%